INTRAPERSONAL INTELLIGENCE AND MOTIVATION IN FOREIGN LANGUAGE LEARNING - Maria del Mar Palenzuela Perez; Noemi Reina Ruz (European Scientific Journal, ESJ, 2014)
The Multiple Intelligences Theory proposes a pluralistic view of mind which takes into account people have different cognitive potential. Thus, suggests the existence of at least eight intelligences of equal rank: the linguistic, logical-mathematical, musical, bodily-kinesthetic, spatial, intrapersonal, interpersonal and naturalist intelligence. This study proposed a programme based in the intrapersonal intelligence in order to increase the students motivation. The result have shown that a methodology which develops the intrapersonal intelligence helps the students to know himself and hence apply this knowledge to develop learning strategies based on their strong points.